Peopling History of the Tibetan Plateau and Multiple Waves of Admixture of Tibetans Inferred From Both Ancient and Modern Genome-Wide Data - He, Guanglin; Wang, Mengge; Zou, Xing; Chen, Pengyu; Wang, Zheng; Liu, Yan; Yao, Hongbin; Wei, Lan-Hai; Tang, Renkuan; Wang, Chuan-Chao; Yeh, Hui-Yuan (Frontiers in Genetics, 2021)
Archaeologically attested human occupation on the Tibetan Plateau (TP) can be traced back to 160 thousand years ago (kya) via the archaic Xiahe people and 30~40 kya via the Nwya Devu anatomically modern human. However, the history of the Tibetan populations and their migration inferred from the ancient and modern DNA remains unclear. Here, we performed the first ancient and modern genomic meta-analysis among 3,017 Paleolithic to present-day Eastern Eurasian genomes (2,444 modern individuals from 183 populations and 573 ancient individuals). We identified a close genetic connection between the ancient-modern highland Tibetans and lowland island/coastal Neolithic Northern East Asians (NEA). This observed genetic affinity reflected the primary ancestry of high-altitude Tibeto-Burman speakers originated from the Neolithic farming populations in the Yellow River Basin. The identified pattern was consistent with the proposed common north-China origin hypothesis of the Sino-Tibetan languages and dispersal patterns of the northern millet farmers. We also observed the genetic differentiation between the highlanders and lowland NEAs. The former harbored more deeply diverged Hoabinhian/Onge-related ancestry and the latter possessed more Neolithic southern East Asian (SEA) or Siberian-related ancestry. Our reconstructed qpAdm and qpGraph models suggested the co-existence of Paleolithic and Neolithic ancestries in the Neolithic to modern East Asian highlanders. Additionally, we found that Tibetans from Ü-Tsang/Ando/Kham regions showed a strong population stratification consistent with their cultural background and geographic terrain. Ü-Tsang Tibetans possessed a stronger Chokhopani-affinity, Ando Tibetans had more Western Eurasian related ancestry and Kham Tibetans harbored greater Neolithic southern EA ancestry. Generally, ancient and modern genomes documented multiple waves of human migrations in the TP’s past. The first layer of local hunter-gatherers mixed with incoming millet farmers and arose the Chokhopani-associated Proto-Tibetan-Burman highlanders, which further respectively mixed with additional genetic contributors from the western Eurasian Steppe, Yellow River and Yangtze River and finally gave rise to the modern Ando, Ü-Tsang and Kham Tibetans.